Upregulation of COPB2 Promotes Prostate Cancer Proliferation and Invasion Through the MAPK/TGF-β Signaling Pathway - Feng, Yanyan; Sun, Chuanyu; Zhang, Lifeng; Wan, Hongyuan; Zhou, Hangsheng; Chen, Yongquan; Zhu, Lijie; Xia, Guowei; Mi, Yuanyuan (Frontiers in Oncology, 2022)
There is increasing evidence that coatomer protein complex subunit beta 2 (COPB2) plays an important role in various cancer types. This study explored the role and the downstream mediators of COPB2 in prostate cancer (PCa). The expression of COPB2 was determined by the Cancer Genome Atlas database and enzyme-linked immunosorbent assay. COPB2 expression was upregulated in PCa tissues and correlated with Gleason score, biochemical recurrence, and poor prognosis. The functional roles of COPB2 in PCa were verified through a series of experiments. Knocking down COPB2 expression inhibited the growth and clonogenesis of PCa cells, promoted cell apoptosis, and inhibited the ability of scratch repair, invasion of PCa cells, and tumor growth in Nude mice. To analyze downstream signaling pathways, ingenuity pathway analysis, GSEA, and whole-genome expression spectrum GeneChip analysis were used. Western blot revealed that COPB2 expression promoted the proliferation and invasion of PCa cells by regulating the MAPK/TGF-β signaling pathway. The interacting protein (nuclear protein 1, NUPR1) was identified via Co-IP, real-time PCR, Western blot, and TCGA database in sampled tissues. The expressions of the interaction proteins NUPR1 and COPB2 were negatively regulated by each other. COPB2 could be a new biomarker for PCa diagnosis and monitoring and to provide a theoretical basis for identifying effective drug intervention targets through in-depth mechanistic studies.